2013
DOI: 10.1186/1743-422x-10-171
|View full text |Cite
|
Sign up to set email alerts
|

HBV and HCV seroprevalence and their correlation with CD4 cells and liver enzymes among HIV positive individuals at University of Gondar Teaching Hospital, Northwest Ethiopia

Abstract: BackgroundThe co-existence of viral hepatitis caused by HBV and HCV become common causes of severe liver complication and immunological impairment among HIV infected individuals. The aim of this study was to assess the seroprevalence of HBV and HCV and their correlation with CD4 and liver enzyme levels among HAART naïve HIV positive individuals.MethodA Cross-sectional study was conducted from March-May, 2011 at University of Gondar Teaching Hospital, Northwest Ethiopia. HBV and HCV serological tests and liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
41
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 41 publications
30
41
10
Order By: Relevance
“…The reason for such variations in co-infection rate among HIV infected patients could possibly be due to difference in the distribution of these viruses in the various geographic locations, recruitment setting, sample size and ethnic variation. In this study the prevalence of HIV-HBV co-infection was slightly higher in males than females (2.6% vs. 2.08%) which also resembles with study by Wondimeneh et al [12].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The reason for such variations in co-infection rate among HIV infected patients could possibly be due to difference in the distribution of these viruses in the various geographic locations, recruitment setting, sample size and ethnic variation. In this study the prevalence of HIV-HBV co-infection was slightly higher in males than females (2.6% vs. 2.08%) which also resembles with study by Wondimeneh et al [12].…”
Section: Discussionsupporting
confidence: 79%
“…The finding is close to what has been reported from Addis Ababa (6.0%) by Abera et al [20]. The observed 4.7% HIV-HBV co-infection rate was lower compared with the study in North West Ethiopia which reported 5.6% [12]. Conversely, HIV-HBV co-infection rate of this study was higher as compared to worldwide HBV prevalence which was 3.1% [21] [22,23], both from Addis Ababa and lower than study in Kenya (6%) and Nigeria (6%) [19,24].…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…This is higher than the average found in available sources: 34 years in the study of Chloe L. Thio et al (Thio et al, 2013), 36 years in that of Attia et al (Attia et al, 2012), 32 years in that realized by Yitayih M. et al (Yitayih, Meseret, Fanaye, & Yeshambel, 2013), 38 years in the work of H. Diop-Ndiaye et al (Diop-Ndiaye et al, 2008). This could be explained by the youth of the overall African population but also by the fact that the population is sexually active at this age.…”
Section: Discussioncontrasting
confidence: 41%